CONSUMER PERCEPTION, BRAND EXPERIENCE AND PURCHASE INTENTION OF CHINESE MOBILE PHONES IN MANADO - Limbongan, Milka Yodiah; Saerang, David Paul Elia; Mekel, Peggy Adeline (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2014)
The growth of mobile phone users are increasing tremendously every year. The fact also shows that many vendors compete to sell mobile phone products including Chinese vendors. With the cheap image of Chinese products and their product quality have raised the issue to investigate the perception among customer and brand experience that people got. The aim of this study is to analyze the impact of consumer perception and brand experience on purchase intention of Chinese mobile phones in Manado. This study implements qualitative research, and there are 8 informants as research samples. The result shows that both, consumer perception and brand experience give an influence to people to have intention to purchase Chinese mobile phones and also shows that brand experience give the most influence to people not only to have intention but also to decide to purchase product. This research suggests Chinese mobile phones seller to build a good perception about Chinese mobile phone in terms of quality and drafting various managerial strategies to increase the purchase intention, by emphasizing the different perspectives of customer brand experience. Keywords: consumer perception, brand experience, purchase intention